2014
DOI: 10.3844/ajassp.2014.1310.1320
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Frontier Approach for Measuring Technical Efficiency of Small-Scale Improved Salt Production in Guinea

Abstract: Salt production is a major driving force behind the loss of mangrove in Guinea. As the traditional salt production causes increasing deforestation, the intensive exploitation of mangrove resources has now reached a critical threshold. Therefore, improved techniques using sunlight as the source of energy has been introduced as an alternative to the traditional salt production techniques which consumes a significant amount of mangrove wood. Therefore, it's of interest to examine the efficiency of the new salt pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…This finding confirms the results of previous studies conducted by Idiong (2007), Tijani (2006). However, a study (Balde et al, 2014c) conducted in the same site focusing on the technical efficiency of salt production found that younger salt producers were more efficient than the older ones. With respect to education level, it is significant but has a negative impact (positive impact on the technical inefficiency) to the technical efficiency of the mangrove rice production.…”
Section: Stochastic Frontier Production and Estimation Of Technical Isupporting
confidence: 83%
See 2 more Smart Citations
“…This finding confirms the results of previous studies conducted by Idiong (2007), Tijani (2006). However, a study (Balde et al, 2014c) conducted in the same site focusing on the technical efficiency of salt production found that younger salt producers were more efficient than the older ones. With respect to education level, it is significant but has a negative impact (positive impact on the technical inefficiency) to the technical efficiency of the mangrove rice production.…”
Section: Stochastic Frontier Production and Estimation Of Technical Isupporting
confidence: 83%
“…This implies that the investment in labor forces in the mangrove rice production in Koba (Boffa prefecture) does not bring improvement in productivity. Therefore, a previous study (Balde et al, 2014c) related to the technical efficiency measurement in the same study area found that the investment in labor could bring a significant improvement in performance of salt production. In addition, a study (Balde et al, 2013a) on mangrove rice production in the coastal area of Dubreka prefecture, in Guinea also found that among all inputs included under the average variable costs (fertilizer cost, pesticide cost, herbicide cost, hired labor cost, local and improved varieties cost), the hired labor per hectare represented the highest variable input in terms of cost (77 to 97% of variable cost according the different type of rice varieties under consideration).…”
Section: Stochastic Frontier Production and Estimation Of Technical Imentioning
confidence: 99%
See 1 more Smart Citation